2009
DOI: 10.1016/j.jesp.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

When failing feels good—Relative prototypicality for a high-status group can counteract ego-threat after individual failure

Abstract: To cite this version:Marc-André Reinhard. When failing feels good -Relative prototypicality for a high-status group can counteract ego-threat after individual failure. Journal of Experimental Social Psychology, Elsevier, 2009, 45 (4) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 58 publications
9
39
1
1
Order By: Relevance
“…Previous research has suggested that the members of high-status groups engage in different reactions to failure, compared to those of low-status groups (Reinhard, Stahlberg, & Messner, 2009); research also suggests that high-status group members do not value the domains in which lower status groups excel (Schmader et al, 2001). Thus, it is noteworthy that we replicated this effect using a FIGURE 2 Stereotype endorsement as a function of gender and version (Experiment 2).…”
Section: Discussionsupporting
confidence: 52%
“…Previous research has suggested that the members of high-status groups engage in different reactions to failure, compared to those of low-status groups (Reinhard, Stahlberg, & Messner, 2009); research also suggests that high-status group members do not value the domains in which lower status groups excel (Schmader et al, 2001). Thus, it is noteworthy that we replicated this effect using a FIGURE 2 Stereotype endorsement as a function of gender and version (Experiment 2).…”
Section: Discussionsupporting
confidence: 52%
“…People therefore strive to affiliate with groups that are positively distinct from other groups lower in prestige or social value (Hogg, 2006). Reinhard, Stahlberg, and Messner (2009) also demonstrated that members of high‐status groups, but not members of low‐status groups, reacted with an increase in self‐esteem through heightened in‐group identification after a poor performance on a fictitious intelligence test. Moreover, based on social identity theory, identifying with an in‐group with low social value has little impact on restoring positive self‐evaluation because it ensures a negative social identity.…”
Section: The Role Of In‐group Representation and Social Value In The mentioning
confidence: 97%
“…Recent research has investigated the male role norm, a role ''imposed upon men to shape the way they act'' (Thompson, Grisanti, & Pleck, 1985, p. 414). The male role norm comprises aspects such as achievement, dominance, toughness, and importantly, avoiding everything feminine (Thompson et al, 1985), for example, success on a ''feminine knowledge test''-a test on which women typically score higher than men (Rudman, Dohn, & Fairchild, 2007; also see Reinhard, Stahlberg, & Messner, 2009). Relatedly, recent theorizing has considered psychological (heterosexual) maleness to be a precarious status (Vandello, Bosson, Cohen, Burnaford, & Weaver, 2008) that must be earned and demonstrated over and over (for a review, see Bosson & Vandello, 2011).…”
Section: Social-cultural Correlates Of Anti-gay Attitudesmentioning
confidence: 99%